Utilization of the Library as a Learning Resource for Students of the Department of Islamic Religious Education - Asriani Abbas (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The library is one of the important learning resources for students who are pursuing higher education. Libraries offer access to various information and materials needed to enrich and complete the learning process. However, literature that focuses on the use of libraries among students majoring in Islamic religious education is still minimal. This qualitative descriptive research aims to find out how students majoring in Islamic religious education at the Muhammadiyah Sinai Islamic College use the library as a learning resource. Methodology: This study uses qualitative research methods to collect data. The research sample consisted of librarians and students majoring in Islamic religious education at the Muhammaduyah Sinjai Islamic College. Interview instruments were used to collect data, and the data analysis technique used was Miles & Huberman, which involved an iterative process of coding and identifying themes. Main Findings: The research findings reveal that students majoring in Islamic religious education utilize the library primarily to access religious texts and books, participate in group discussions, and study. This study also found that librarians facilitate students' access to information by offering reference and circulation services. In addition, this study notes that the library atmosphere provides students with a conducive environment for learning. Novelty/Originality of this study: This research is a significant contribution to the body of knowledge in the field of Islamic religious education at the Muhammaduyah Sinjai Islamic College because it explores the use of library resources by students majoring in that field. This study provides insight into the unique challenges students face in accessing library resources and offers recommendations for enhancing their learning experience. This study is original in its approach and offers a new perspective on the use of the library as a learning resource for students of Islamic religious education at the Muhammaduyah Sinjai Islamic College.. Purpose of the study: The library is one of the important learning resources for students who are pursuing higher education. Libraries offer access to various information and materials needed to enrich and complete the learning process. However, literature that focuses on the use of libraries among students majoring in Islamic religious education is still minimal. This qualitative descriptive research aims to find out how students majoring in Islamic religious education at the Muhammadiyah Sinai Islamic College use the library as a learning resource. Methodology: This study uses qualitative research methods to collect data. The research sample consisted of librarians and students majoring in Islamic religious education at the Muhammaduyah Sinjai Islamic College. Interview instruments were used to collect data, and the data analysis technique used was Miles & Huberman, which involved an iterative process of coding and identifying themes. Main Findings: The research findings reveal that students majoring in Islamic religious education utilize the library primarily to access religious texts and books, participate in group discussions, and study. This study also found that librarians facilitate students' access to information by offering reference and circulation services. In addition, this study notes that the library atmosphere provides students with a conducive environment for learning. Novelty/Originality of this study: This research is a significant contribution to the body of knowledge in the field of Islamic religious education at the Muhammaduyah Sinjai Islamic College because it explores the use of library resources by students majoring in that field. This study provides insight into the unique challenges students face in accessing library resources and offers recommendations for enhancing their learning experience. This study is original in its approach and offers a new perspective on the use of the library as a learning resource for students of Islamic religious education at the Muhammaduyah Sinjai Islamic College..